IMPROVING METHODOLOGICAL APPROACHES TO FINANCIAL ASSET ACCOUNTING - Kholmirzaev Ulugbek Abdulazizovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
There are general and specific methods in accounting and analysis. The conceptual framework of financial accounting and reporting is an important fundamental structure on which general and specific methods are based. Hence, the more thoroughly this fundamental structure is developed, the more reliable and acceptable the methods derived from it will be